(untitled) (River Edge, N.J., 2005)
Bioluminescence and chemiluminescence are among the most important technologies in the life sciences. This latest volume of the long-running biannual Bioluminescence and Chemiluminescence symposium series presents the latest developments in the fundamental and applied aspects of bioluminescence and chemiluminescence. The book covers the fundamental aspects of bioluminescence, including beetle, marine bacterial and Cypridina bioluminescence, and the fundamental aspects of chemiluminescence, including 1,2-dioxetanes. It also presents recent developments in instrumentation and devices and a wide range of applications of bioluminescence and chemiluminescence. The applications are succinctly described and include applications of luminescence in antioxidant research, phagocytosis, microbiology, ecology, food and environmental testing, immunoassay, enzyme assays, DNA probe assays, and reporter gene and gene expression assays.
Keywords: Chemiluminescence,Chemiluminescence assay,Bioluminescence,Bioluminescence assay,Phát quang bằng phản ứng hóa học,Thí nghiệm sự phát quang bằng phản ứng hóa học,Phát quang sinh học